Heart transplant recipient with features of COVID-19 infection: First case report from India - Dhruva Sharma; Sunil Dixit; Anil Sharma (Indian Journal of Transplantation, 2020)
A 16-year-old boy has been reported 3 months postcardiac transplantation with chief complaints of nausea, vomiting, pain in abdomen, and fever. The patient had remarkably increased serum lactate dehydrogenase levels, triglycerides, serum amylase, and serum lipase. The B-type natriuretic peptide level more than 35,000 ng/mL and troponin T was increased (0.57 μg/ml). Last known concentration of tacrolimus was 9 ng/ml. Supraventricular tachycardia was remarkable on electrocardiogram. His computed tomographic findings revealed bilateral pneumothorax with bilateral pleural effusion with an opacity seen in the right upper lobe. Bedside echo revealed dilated right atrium and right ventricle with left ventricular ejection fraction of 60%. He was kept on immunosuppression of mycophenolate mofetil 360 mg (2 tablets twice a day) and tacrolimus (2.5 mg twice a day). His reverse transcriptase-polymerase chain reaction throat swabs of the patient were sent for testing 2019-nCoV and were found to be negative. The patient could not be revived in spite of all medical management.